Magic: The gathering's narrative as an aesthetic experience - Oliver, Pio Alfonso T. (Animo Repository, 2025)
This paper examines the card game Magic: the Gathering (shorthanded to Magic, MtG, or MTG) and seeks to show that its narrative elements may be able to provide an aesthetic experience based on the framework of John Dewey. Dewey (1934) wrote about the aesthetic experience as different from the normal, mundane everyday experience. The aesthetic experience is described as being distinct and worthwhile, with the person focused on that experience and having strong emotional ties to it. The mundane experiences however, which Dewey referred to as anesthetic experiences, did not keep the person focused on it or lacked the emotional ties of the aesthetic. They are differentiated based on qualities that the aesthetic experience possessed which are not found in the anesthetic. Dewey’s experience provides a framework that has often been used to discuss the aesthetic value of traditional artistic mediums. The arrival of new mediums however offer an interesting use of Dewey’s experience in showcasing their possible aesthetic experience. One such medium is games. Different forms of games have begun to gain recognition and the argument has arisen for their place within art. Video games are the prime example of this, with many arguing for their elevation as artforms. Card games and older modes of games, such as Magic, have equally retained their popularity and cultural significance among those who play them. They suffer however a lack of literature which could highlight the significance they provide in the attainment of aesthetic experiences by those who play them specifically through the narrative game elements present within it. This paper examines a case study by Pietari Majuri of Magic’s narrative elements and how it affects player enjoyment. This paper will showcase that such narrative roleplaying elements elevates the game of Magic into providing aesthetic experiences.